The Implementation of The BSCS 5E Model Based on Multiple Representations in Ecosystem Materials on Problem Solving and Metacognitive Abilities - Purwaningsih, Sri Dyah Ayu; Mubarok, Ibnul (Journal of Biology Education, 2021)
This study analyses the students' problem solving and metacognitive abilities by applying the BSCS 5E model based on multiple representations to ecosystem material. This research is a pre-experiment using the One-Shot Case Study design. The research pupils were students of class X SMA N 1 Donorojo in the 2019/2020 academic year. The research sample was class X MIPA 2 and X MIPA 5, taken by purposive sampling. The methods used in data collection include tests, interviews and questionnaires. The results showed that the problem-solving ability was in the "medium" category with an average score of 58.8 and the students' final score was in the "medium" category with an average of 60.4. Metacognitive abilities are in the "ok" category. The study journal is in the "high" category. Also the implementation of the learning model is in the "high" category. The calculation results obtained rcount ÃªÅ¾Å  0.509 while rtable with dk ÃªÅ¾Å  65 and a significant level of 5% is 0.244. Because rcount> rtable, HO reject and accept H1 means a significant relationship between problem-solving and metacognitive abilities. Contribution of problem-solving abilities to metacognitive abilities was 26%. Based on the results of the study, it can be concluded that the students ' problem-solving abilities are in the "medium" category and the students' metacognitive abilities are "ok" by applying the BSCS 5E model based on multiple representations on ecosystem material.